Problematics of Learning Javanese Script And Alternative Solutions: A Literature Review - Yusuf Nur Kholiq; Endang Nurhayati; Purwadi Purwadi (Journal of Innovation in Educational and Cultural Research, 2024)
Various problems are still encountered when learning a Javanese script in schools. These problems need to be known so that alternative solutions can be found. This study aims to 1) describe the problems of learning Javanese script and 2) identify possible solutions to the problems of learning Javanese script. This study is a literature study. The research data is information about the problems of learning Javanese script. The sources of literature studies in this study are journal articles accessed through Google Scholar, Research Gate, and Scopus. The data analysis technique in this study used the content analysis technique. The technique for checking the validity of this study used the theory triangulation technique. The results of this study showed that there were six problems in learning Javanese script. From an internal perspective, the problems are students not memorizing Javanese script, low motivation, students' perception that Javanese script is difficult, and low intensity of Javanese script use. From an external perspective, the problems of learning Javanese script are limited Javanese script teaching resources and Javanese script teaching that is still conventional. Alternative solutions to these problems are using relevant learning media, methods, and learning models based on student characteristics, making it a habit, and instilling meaningful understanding. The results of this study can be used as a guide for teachers in identifying and overcoming difficulties in learning Javanese script.